Κραδίᾳ γνωστὸς ἔνεστι τύπος (Meleager, Anth. Pal. 5.212.4): Self-Reflexive Engagement with Lyric Topoi in Erotic Epigram - Regina Höschele (Aitia, 2018)
Sarah Mace, in a 1993 article, brilliantly traced the usage of δηὖτε in Archaic lyric, where the widespread topos of “Love . . . yet again” not only evoks the speaker’s personal experience of repeated erotic desire, but also the recurrence of love’s overwhelming onset throughout the genre. When Hellenistic epigrammatists write about their eros several centuries later, they manifestly engage with this and other lyric topoi, marking their experience of love as something well-known from the erotic tradition: it is not least the knowledge of their lyric models that enables them (and their readers) to correctly diagnose amatory symptoms and identify erotic symbols as such. Although such metapoetic play is something we readily associate with Hellenistic poetry, the potential for self-conscious evocation of the poetic tradition and generic conventions is already inherent in Archaic lyric itself. The present article looks at these earlier instances of self-reflexivity in comparison with the modes of allusion we encounter in erotic epigrams. By delineating similarities and differences in the generic and/or intertextual self-awareness of Archaic and Hellenistic poets, it hopes to shed new light on the inner workings of allusion in different literary contexts.